Oxford collocations dictionary for students of English - McIntosh, Colin (Oxford University Press, 2009)
The dictionary that helps students write and speak natural-sounding English, now in a new edition with CD-ROM. Which words usually go together? This dictionary shows you the common word combinations (collocations) that are essential for natural-sounding British and American English. Completely revised and extended, the new edition has over 250,000 collocations and over 75,000 examples.